Performing Mentorship in Collaborative Research Teams - Armos, Nicole; Chasse, Callista (Papers on Postsecondary Learning and Teaching, 2022)
This paper shares preliminary findings from a reflective inquiry into the nature of collaboration and mentorship through digital spaces within a national SSHRC-funded research team the authors form a part of. Our research collaboration has been marked by particularly close friendships, co-creation and mutual learning that have helped to deepen our research and provide a meaningful and enriching experience for everyone involved. Proposing that mentorship and collaboration can be viewed as a performance, which can be enacted in diverse ways depending on the context and intention, we share the digital and arts-based methods our team uses to both foster mentorship relationships and routinely reflect on how we are performing and experiencing mentorship within our team in order to identify and respond to our emerging needs, challenges and opportunities to enrich our collaboration.
Papers on Postsecondary Learning and Teaching, Vol. 5 (2022): Papers on Postsecondary Learning and Teaching